Magnetic-field sensor with self-reference characteristic based on a magnetic fluid and independent plasmonic dual resonances - Ren, Kun; Ren, Xiaobin; He, Yumeng; Han, Qun (Beilstein Journal of Nanotechnology, 2019)
A magnetic-field sensor with self-reference characteristic based on metal–dielectric–metal (MDM) plasmonic waveguides and a magnetic fluid (MF) is proposed and theoretically investigated. Independent dual resonances are supported by the coupled resonator–waveguide system. The physical mechanisms of dual resonances are analyzed by the temporal coupled-mode theory. The transmission response to an external magnetic field is explored by using the remarkable tunability of the refractive index of the MF. Based on the different dependence of two resonances on the external field, a magnetic-field sensor with self-reference characteristic is achieved. The magnetic-field nanosensor shows an excellent performance with a high sensitivity of 27 pm/Oe, i.e., 270 pm/mT. The proposed sensor takes advantage of the refractive-index tunability of the MF and the compactness of the MDM waveguide structure. This research may open new opportunities to design nanoscale magnetic sensors with good performance.
Keywords: dual resonance; magnetic fluid; magnetic sensor; plasmonic waveguide; self-reference; surface plasmon polaritons